Rapid Screening for C3435t Polymorphism in Exon 26 of the Multi-Drug Resistance (MDR1) Gene in Malay Patients with Acute Leukemia - Yahaya, Badrul Hisham (Penerbit Universiti Sains Malaysia, 2005)
The over expression of P-glycoprotein has been found to be associated with therapy resistance in hematological malignancies including acute leukemias. Recently, a single nucleotide polymorphism (SNP) in exon 26 (C3435T) in the MDR1 gene has shown to have functional consequences with altered expression of P-gp. Denaturing HPLC has been established as a rapid method for screening SNP in the form of heteroduplex of the DNA samples under partially denaturing condition.